2017
DOI: 10.1038/ncomms16040
|View full text |Cite
|
Sign up to set email alerts
|

BCAT1 controls metabolic reprogramming in activated human macrophages and is associated with inflammatory diseases

Abstract: Branched-chain aminotransferases (BCAT) are enzymes that initiate the catabolism of branched-chain amino acids (BCAA), such as leucine, thereby providing macromolecule precursors; however, the function of BCATs in macrophages is unknown. Here we show that BCAT1 is the predominant BCAT isoform in human primary macrophages. We identify ERG240 as a leucine analogue that blocks BCAT1 activity. Selective inhibition of BCAT1 activity results in decreased oxygen consumption and glycolysis. This decrease is associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
141
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(155 citation statements)
references
References 65 publications
6
141
0
1
Order By: Relevance
“…In corroboration with these studies, a recent report showed that in activated macrophages, IRG1/itaconate axis is utilized for the catabolism of branched‐chain amino acids (BCAA). Blocking BCAA by leucine analogue, ERG240 resulted in decreased pro‐inflammatory transcriptome signature . Together, these studies suggest the role of itaconic acid in mediating the inflammatory and microbicidal functions of M1 macrophages.…”
Section: Metabolic Regulation Of Macrophage Polarizationmentioning
confidence: 72%
“…In corroboration with these studies, a recent report showed that in activated macrophages, IRG1/itaconate axis is utilized for the catabolism of branched‐chain amino acids (BCAA). Blocking BCAA by leucine analogue, ERG240 resulted in decreased pro‐inflammatory transcriptome signature . Together, these studies suggest the role of itaconic acid in mediating the inflammatory and microbicidal functions of M1 macrophages.…”
Section: Metabolic Regulation Of Macrophage Polarizationmentioning
confidence: 72%
“…In one of these studies, HDAC inhibition yielded clinical benefits for patients with the IL‐1‐driven Schnitzler syndrome . As for the metabolic reprogramming of trained cells, there are examples of animal models in which metabolic inhibitors have been used to treat inflammatory diseases . For example, a recent study revealed that inhibition of a specific metabolic enzyme reduced disease severity in two murine models of autoimmune disease (e.g.…”
Section: Modulating Il‐1 Via the Induction Of Trained Immunitymentioning
confidence: 99%
“…For example, a recent study revealed that inhibition of a specific metabolic enzyme reduced disease severity in two murine models of autoimmune disease (e.g. rheumatoid arthritis and glomerulonephritis) . Further research is needed in order to determine whether trained immunity mechanisms play a role in these conditions and if these indeed can be modulated in vivo by therapeutics targeting epigenetic and metabolic processes.…”
Section: Modulating Il‐1 Via the Induction Of Trained Immunitymentioning
confidence: 99%
“…Leucine influx is mediated by solute carrier family 7 member 5 (SLC7A5). Treatment with a selective inhibitor of BCAT1 reduced inflammation and macrophage infiltration in target organs in murine models of RA and crescentic glomerulonephritis [90]. BCAT exists in two isoforms, mitochondrial BCAT2 and cytosolic BCAT1.…”
Section: Branch Chain Amino Acid and Glutamine Metabolismmentioning
confidence: 97%
“…Here, we will focus on BCAAs, especially leucine and glutamine metabolism. In human monocyte-derived macrophages, BCAT1 is the most abundantly expressed BCAT isoform [90]. Leucine influx is mediated by solute carrier family 7 member 5 (SLC7A5).…”
Section: Branch Chain Amino Acid and Glutamine Metabolismmentioning
confidence: 99%